Pemberdayaan Komunitas Adat Terpencil di Kabupaten Indragiri Hilir: Sinkronisasi Peraturan Menteri Sosial Republik Indonesia No. 9 Tahun 2012 dan Prinsip Desentralisasi Kewenangan Daerah - Hendra Rizki Fauzi; Jamri Jamri; Didi Syaputra (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This normative legal study analyzes the synchronization between Minister of Social Affairs Regulation No. 9 of 2012 on the Empowerment of Remote Indigenous Communities (KAT) and the principle of regional authority decentralization under Law No. 23 of 2014 in Indragiri Hilir Regency, focusing on the Duanu Tribe community in coastal areas. Employing a descriptive-analytical juridical normative approach through library research and statutory interpretation, the study reveals that conceptually, harmonization space exists through the adoption of Permensos substance into local regulations, development planning documents (RPJMD-RPJMDes), and cross-sectoral coordination. However, implementation faces obstacles including the absence of specific local regulations, data and budget limitations, extreme geographical accessibility challenges, and cultural resistance. Strengthening efforts are recommended through special Perda/Perbup for KAT, integration of KAT indicators into RPJMD, digital SOPs integrated with SIKS, civil servant training, and multi-stakeholder participation to achieve sustainable, locally adaptive empowerment. This study contributes policy recommendations for inclusive development of KAT in autonomous regions with complex geography